1968, the world transformed - Fink, Carole; Gassert, Philipp; Junker, Detlef (Publications of the German Historical Institute, 1998)
"1968: The World Transformed" presents a global perspective on the tumultuous events of the most crucial year in the era of the Cold War. By interpreting 1968 as a transnational phenomenon, authors from Europe and the United States explain why the crises of 1968 erupted almost simultaneously throughout the world. Together, the eighteen chapters provide an interdisciplinary and comparative approach to the rise and fall of protest movements worldwide. The book represents an effort to integrate international relations, the role of media, and the cross-cultural exchange of people and ideas into the history of that year. 1968 emerges as a global phenomenon because of the linkages between domestic and international affairs, the powerful influence of the media, the networks of communication among activists, and the shared opposition to the domestic and international status quo in the name of freedom and self-determination.